1979
DOI: 10.1073/pnas.76.2.750
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthetase purified to homogeneity from human leukemic cells.

Abstract: Thymidylate synthetase (5,10-methylenetetrahydrofolate:dUMP C-methyltransferase, EC 2.1.1.45) from a human leukemic cell line has been purified to homogeneity with one-step affinity column chromatography. The purified enzyme has a specific activity of 3.8 jtmo /min per mg of protein, which corresponds to a turnover number of 250. These are the highest values reported for a thymidylate synthetase from neoplastic tissue. A ratio of 1.7 mol of 5-fluoro-2'.deoxyuridylate binds per mol of enzyme in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…13,25 Trichloroacetic acid-insoluble material was collected by filtration through glass fiber filters and analyzed for radioactivity in a scintillation counter. In the indicated experiments, the amount of TS enzyme was normalized to the amount of total protein in the cell extract, which was determined by the DC Protein Assay (BioRad).…”
Section: Analysis Of Ts Enzyme and Mrna Levelsmentioning
confidence: 99%
“…13,25 Trichloroacetic acid-insoluble material was collected by filtration through glass fiber filters and analyzed for radioactivity in a scintillation counter. In the indicated experiments, the amount of TS enzyme was normalized to the amount of total protein in the cell extract, which was determined by the DC Protein Assay (BioRad).…”
Section: Analysis Of Ts Enzyme and Mrna Levelsmentioning
confidence: 99%
“…The amount of the TS enzyme in cytosol was determined by measuring the binding of 3H-FdUMP in the presence of 5,10-CHz-FH4 according to the published procedures (Santi et al, 1974a;Lockshin et al, 1979). The number of FdUMP binding sites can be taken as a direct measure of the enzyme level in the cell.…”
Section: Determination Of Ts Levelsmentioning
confidence: 99%
“…Phan et al (2001) found that TS functions as an RNA binding protein that regulates the expression of its own mRNA translation, the emergence of resistance to the treatment is often related to the increased level of TS in cancer cells, which have been linked to the elimination of TS binding to its own mRNA upon drug binding. During the early stage, TS was obtained from human cells (Lockshin et al, 1979;Dolnick et al, 1977). With the development of gene recombination and prokaryotic expression system, it is feasible to expression human TS in E. coli.…”
Section: Introductionmentioning
confidence: 99%